Testing the hysteresis effect in the US state-level unemployment series - Omay, Tolga; Ozcan, Burcu; Shahbaz, Muhammed (Routledge Journals, Taylor & Francis Ltd, 2020)
This paper re-examines the stochastic time series behaviour of the monthly unemployment rate in 50 states of the United States (US) for the period 1976-2017 using a number of state-of-the-art unit root tests. The new developments incorporate structural break, nonlinearity, asymmetry, and cross-sectional correlation within panel-data estimation including the use of a sequential panel selection method. While not previously considered, sequential panel selection enabled us to determine and separate the stationary and nonstationary series in the sample. The empirical findings are in support of the stationarity of unemployment rate in 47 states. The findings confirm a natural rate hypothesis for the labour markets in the most US states, indicating that labour market shocks have solely temporary effects on state-level unemployment. This empirical study provides significant state-specific policy implications.
Keywords: Linear nonlinear and structural break; panel unit root; cross-section dependency; common correlated estimator CCE; hysteresis